The Limits of Arbitrator Immunity and Institutional Responsibility in the Annulment of Arbitration Awards: A Normative Study under Indonesian Arbitration Law - Khairunnisa Siregar; Najwa Fadila; Nabila Putri Aulia; Randy Harahap; Mhd Imran Pradipta (Jurnal Sahabat ISNU SU, 2026)
Arbitration has become a preferred mechanism for resolving commercial disputes because it offers confidentiality, procedural flexibility, efficiency, and finality of decisions. Although arbitral awards are generally final and binding, Indonesian law recognizes a limited mechanism for their annulment under Article 70 of Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution, allowing judicial intervention where an award is based on forged documents, concealed decisive evidence, or fraudulent conduct during arbitral proceedings. This study examines the legal basis for annulment, the legal responsibility of arbitrators and arbitration institutions following annulment, the procedural framework governing annulment applications, and the implications of annulment for arbitral immunity, legal certainty, and public confidence in arbitration. The research employs normative legal research using statutory, conceptual, comparative, and case approaches. Primary legal materials consist of Indonesian arbitration legislation, while secondary materials include legal doctrines, scholarly books, journal articles, international arbitration principles, and selected judicial decisions. The collected materials are analyzed qualitatively through systematic, conceptual, and comparative legal interpretation. The study finds that annulment constitutes an exceptional form of judicial control rather than an appellate review of arbitral awards. It further demonstrates that arbitrators and arbitration institutions generally benefit from functional immunity derived from their quasi-judicial role, although such immunity is not absolute where fraud, bad faith, conflicts of interest, or acts exceeding arbitral authority are legally established. The study concludes that balancing the principle of finality with institutional accountability is essential to preserving legal certainty and public confidence, while strengthening ethical standards, institutional oversight, procedural transparency, and clearer regulation of arbitral immunity will enhance the credibility and accountability of Indonesia's arbitration system.